Changes in EPA and DHA during supplementation with omega-3 fatty acids and incident cardiovascular events: secondary analysis from the OMEMI trial. (14th October 2021) - Myhre, P; Smith, E B; Kalstad, A A; Tveit, S; Laake, K; Smith, P; Nilsen, D W T; Tveit, A; Solheim, S; Arnesen, H; Seljeflot, I; ,
Abstract: Background: In the OMEMI trial, elderly post-MI patients did not achieve reduction in cardiovascular events from supplementation of 1.8g n-3 polyunsaturated fatty acids (PUFA). In two recent trials of hypertriglyceridaemic patients the REDUCE-IT trial demonstrated an association between high levels of serum eicosapentaenoic acid (EPA) and reduced risk of CV events with 4 g/day icosapent ethyl supplements while in the STRENGTH trial no such association was present in patients treated with 4 g/day of EPA+ docosahexaenoic acid (DHA). Purpose: To assess associations between changes in concentrations of EPA and DHA during two years supplementation with n-3 PUFA and incident cardiovascular events in the OMEMI trial. Methods: In the randomized controlled OMEMI trial, 1014 elderly patients with a recent acute myocardial infarction (AMI) were treated with 1.8g/day of EPA and docosahexaenoic acid (DHA) or placebo for two years, and followed for the primary outcome of MACE (AMI, coronary revascularization, stroke or heart failure hospitalization) and secondary outcome of new-onset atrial fibrillation (AF). Serum concentrations of EPA and DHA were measured at inclusion and at study completion by gas chromatography, and reported as % weight of total FA (%wt) in serum phospholipids. Results: Serial EPA and DHA measurements at study inclusion and completion were available in 881 patients (92% of survivors). At baseline EPA and DHA concentrations were (mean±SD) 2.84±1.41 and 5.71±1.35%wt, respectively. Higher baseline EPA and DHA concentrations were associated with previous n-3 PUFA supplementation, lower prevalence of current smoking and diabetes, lower levels of triglycerides and higher levels of HDL-cholesterol (all p<0.05). In patients randomized to n-3 PUFA, EPA and DHA increased with 2.32±1.92 and 0.91±1.19%wt, respectively, whereas in the placebo group EPA and DHA decreased with −0.39±1.37 and −0.43±1.13%wt, respectively. Greater increases in EPA and DHA during follow-up were associated with a lowering of triglyceride concentrations, increasing HDL concentrations, and lower baseline concentrations of EPA and DHA (all p<0.001). Among patients treated with n-3 PUFA (n=438), a greater increase in EPA was associated with a lower risk of incident MACE (HR 0.89 [95% CI 0.78–1.00] per %wt, p=0.059) and higher risk of new-onset AF in patients free of AF at inclusion (n=339): HR 1.31 [1.06–1.62] per %wt, p=0.012 (Figure). There were no such associations for changes in DHA: HR 0.86 (95% CI 0.70–1.05), p=0.13 for MACE and HR 1.29 (0.91–1.83), p=0.16 for new-onset AF. Conclusion: Patients treated with 1.8 g/day n-3 PUFA for two years experienced a doubling of serum EPA concentrations. Greater increases in EPA were associated with a lower risk of MACE, but also a higher risk of new-onset AF. Changes in DHA concentrations were not associated with outcomes, suggesting that EPA may be the more important n-3 PUFA with respect to risk of cardiovascular events. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Oslo University Hospital, Ullevål